Dual-Polarization Dual-Parallel MZM and Optical Phase Shifter Based Microwave Photonic Phase Controller - T. Niu; X. Wang; E. H. W. Chan; X. Feng; B. O. Guan (IEEE Photonics Journal, 2016)
A new microwave photonic phase controlling structure that can realize a continuously tunable 0 $^{°}$ to 360 $^{°}$ phase shift using only one DC voltage control is presented. Unlike other phase controlling structures, the radio-frequency (RF) signal phase shift produced by the new phase controller has a predefined linear relationship with the control voltage. This enables users to easily determine the control voltage needed to realize the desired RF signal phase shift. The microwave photonic phase controller is based on an integrated dual-polarization dual-parallel Mach–Zehnder modulator (DPMZM) and a polarization-dependent optical phase shifter. It is suitable for realizing multiple RF signal phase shifts, which are required in beamforming applications. Experimental results are presented which demonstrate the realization of a continuously tunable $-$ 180 $^{°}$ to 180 $^{°}$ phase shift with little phase and amplitude variations over a wide frequency range, as well as a linear RF signal phase shift to control voltage relationship.